Reasoning and Critical Thinking Through A Qur’an-Integrated Physics E-Module: Evidence from A Senior High School - Hunaidah Hunaidah; Widiasih Widiasih; Amiruddin Takda; Miftahuljannah Muslimin; Md Asri Bin Ngadi (Jurnal Pendidikan Sains Indonesia, 2026)
This study investigates the effect of a Qur’an-integrated physics e-module on senior high school students’ scientific reasoning (SR) and critical thinking (CT). A quasi-experimental pretest–posttest control group design was employed involving 70 grade 10 students from a Tahfiz senior high school in Indonesia. The experimental group (n = 36) learned using the Qur’an-integrated e-module, while the control group (n = 34) received conventional instruction. SR and CT were measured using performance-based tests adapted from established frameworks. Data were analyzed using independent and paired samples t-tests, effect sizes (Cohen’s d), and normalized gain scores. The results showed statistically significant differences between groups in SR (M_exp = 76.11, SD = 3.42; M ctrl = 73.17, SD = 3.50; p < .001; d = 0.85) and CT (M_exp = 72.44, SD = 2.51; M_ctrl = 70.29; SD = 2.49; p < .001; d = 0.86). The experimental group also demonstrated higher gains across physics topics (measurement, motion, and phase change). Indicator-level analysis revealed consistent and parallel patterns of development between SR and CT, suggesting coherent cognitive growth. To further examine these parallel developments, the study introduces an outcome matrix that maps topic-specific gains against cognitive indicators, offering a structured representation of integrated reasoning growth. These findings indicate that Qur’anic reflection embedded within a digital physics module can function as a structured reflective scaffold that strengthens analytical and evaluative thinking. The study provides empirical support for Islamic-integrated science instruction as an effective approach to fostering higher-order thinking in secondary physics education